Menopausal women’s experiences of husband’s support: a negative view - Hassan, Intan Idiana; Hussain, Nik Hazlina Nik; Sulaiman, Zaharah; Kadir, Azidah Abdul; Nor, Mohd Zarawi Mat (Elsevier, 2019)
Objective: This study explores how menopausal women perceived supports provided by their husbands. Methodology: Total of 13 menopausal women recruited using a combination of purposive and snowball techniques from two sources, tertiary hospital and local communities in the state of Kelantan, Malaysia. The in-depth semi-structured interview guided was used to explore how they perceived supports provided by their husbands. The data were then analysed using a thematic analysis. Results: Five (5) themes have emerged which comprises of emotional, instrumental, appraisal, guidance, and sexual supports. One of which was a new theme (sexual intimacy support) that had not been existed previously in other literature reviews. Conclusion: Majority of menopausal women perceived the supports provided by their husband were negative, rather than positive supports that they had hoped. These findings suggest that an education program tool for husbands as a support person is much needed to ensure women walk through the menopause phase in a more meaningful life.